Intracranial hemorrhages in patients with COVID-19: a systematic review of the literature, regarding six cases in an Amazonian population - William de Sousa Lima; Marcelo Henrique Pereira Soares; Eric Homero Albuquerque Paschoal; Joelma Karin Sagica Fernandes Paschoal; Fernando Mendes Paschoal; Edson Bor-Seng-Shu (Arquivos de Neuro-Psiquiatria)
Background Coronavirus disease 2019 (COVID-19) has emerged as a public health emergency worldwide, predominantly affecting the respiratory tract. However, evidence supports the involvement of extrapulmonary sites, including reports of intracranial hemorrhages.